Scorpion Venom Heat-Resistant Peptide Protects Transgenic Caenorhabditis elegans from β-Amyloid Toxicity - Zhang, Xiao-Gang; Wang, Xi; Zhou, Ting-Ting; Wu, Xue-Fei; Peng, Yan; Zhang, Wan-Qin; Li, Shao; Zhao, Jie (Frontiers in Pharmacology, 2016)
Scorpion venom heat-resistant peptide (SVHRP) is a component purified from Buthus martensii Karsch scorpion venom. Our previous studies found SVHRP could enhance neurogenesis and inhibit microglia-mediated neuroinflammation in vivo. Here, we use the transgenic CL4176, CL2006 and CL2355 strains of Caenorhabditis elegans which express the human Aβ1–42 to investigate the effects and the possible mechanisms of SVHRP mediated protection against Aβ toxicity in vivo. The results showed that SVHRP-fed worms displayed remarkably decreased paralysis, less abundant toxic Aβ oligomers, reduced Aβ plaque deposition with respect to untreated animals. SVHRP also suppressed neuronal Aβ expression-induced defects in chemotaxis behavior and attenuated levels of ROS in the transgenic C. elegans. Taken together, these results suggest SVHRP could protect against Aβ-induced toxicity in C. elegans. Further studies need to be conducted in murine models and humans to analyze the effectiveness of the peptide.